ns-µs time-resolved step-scan FTIR of ba3 oxidoreductase from Thermus thermophilus: Protonic connectivity of w941-w946-w927 - Nicolaides, Antonis; Soulimane, Tewfik; Varotsis, Constantinos (My University, 2016)
Time-resolved step-scan FTIR spectroscopy has been employed to probe the dynamics of the ba3 oxidoreductase from Thermus thermophilus in the ns-µs time range and in the pH/pD 6-9 range. The data revealed a pH/pD sensitivity of the D372 residue and of the ring-A propionate of heme a3. Based on the observed transient changes a model in which the protonic connectivity of w941-w946-927 to the D372 and the ring-A propionate of heme a3 is described.
Keywords: Cytochrome ba3; Heme-copper oxidoreductases; Ns time-resolved step-scan FTIR